2012
DOI: 10.1007/s13277-012-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

X-ray repair cross-complementing group 1 Arg399Gln gene polymorphism and susceptibility to colorectal cancer:a meta-analysis

Abstract: X-ray repair cross-complementing group 1 (XRCC1), a DNA repair enzyme, plays a crucial role in the base excision repair by generating a single nucleotide repair patch. It has been demonstrated that the XRCC1 Arg399Gln gene polymorphism was associated with variations in XRCC1 enzyme activity. The aim of this study was to quantitatively summarize the association between the XRCC1 Arg399Gln polymorphism and susceptibility to colorectal cancer (CRC). A comprehensive search of the PubMed, Embase, and China National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Five meta-analyses previously have estimated the association between XRCC1 Arg399Gln polymorphism and CRC susceptibility (Liu et al, 2010;Wu et al, 2013;Zeng et al, 2013;Qin et al, 2015). However, the association remains not fully understood DOI:http://dx.doi.org/10.7314/APJCP.2015.16.8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five meta-analyses previously have estimated the association between XRCC1 Arg399Gln polymorphism and CRC susceptibility (Liu et al, 2010;Wu et al, 2013;Zeng et al, 2013;Qin et al, 2015). However, the association remains not fully understood DOI:http://dx.doi.org/10.7314/APJCP.2015.16.8…”
Section: Discussionmentioning
confidence: 99%
“…Our results are inconsistent with the meta-analysis performed by Zeng et al, which 26 case-control studies with 6,979 cases and 11,470 controls were pooled in the meta-analysis. They have suggested that the XRCC1 Arg399Gln polymorphism was significantly associated with increased risk of CRC in among high quality studies and in Asians, but not in Caucasians (Zeng et al 2013). Lu et al, in a meta-analysis suggests that there is an obvious association between the XRCC1 Arg399Gln polymorphism and increased risk of CRC in East Asians .…”
Section: 3285 Association Of Xrcc1 Arg399glnpolymorphism and Colorecmentioning
confidence: 99%
“…Previous meta-analyses indicated that the XRCC1 Arg399Gln polymorphism is associated with the risk of bladder cancer (Mao et al, 2013), colorectal cancer (Zeng et al, 2013), and lung cancer (Dai et al, 2012). However, this polymorphism is not significantly associated with the risk of esophageal cancer (Li et al, 2013) and gastric cancer (Liu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the c.839G>A (p.Arg280His) polymorphism, a lack of colorectal cancer risk association was reported in a meta‐analysis involving seven studies with 3505 cases and 4636 controls . On the other hand, for the c.1196A>G (p.Gln399Arg) polymorphism, although one meta‐analysis involving 22 studies with 6291 cases and 10 289 controls found a lack of significant risk association, another meta‐analysis involving 26 studies with 6979 cases and 11 470 controls found that the variant allele was associated with an increased colorectal cancer risk . In the latter study, when low quality studies (i.e.…”
Section: Dna Repair Genesmentioning
confidence: 99%